Antecedents and Consequences of Employee Job Satisfaction in Indonesia - Darwin Lie; Sofiyan Sofiyan; Robert Tua Siregar; Hery Pandapotan Silitonga; Susanti Sri Rezeki Lubis (Applied Quantitative Analysis, 2021)
Factors that encourage job satisfaction include the application of transformational leadership from a leader in the company. The existence of cultural diversity also contributes to the level of employee job satisfaction. Then the implementation of organizational commitment is also essential to increase employee satisfaction at work. This study deals with the antecedents and consequences of employee work satisfaction, including transformational leadership, culture diversity, and organizational commitment as antecedents and organizational citizenship behavior (OCB) and employee performance as a consequence. The research instrument used a questionnaire distributed to 280 employees who worked in cigarette factories and tapioca flour factories in Pematangsiantar City. For data analysis, this research uses the Smart PLS application with the PLS-SEM approach oriented. This research concludes that transformational leadership and culture diversity has a significant impact on work satisfaction. On the other hand, the results of this research also conclude that organizational commitment does not significantly impact work satisfaction. Furthermore, this research also confirms that work satisfaction significantly affects organizational citizenship behavior (OCB) and employee performance. Then this study was only carried out in one city so that no specific data comparison could be obtained and only focused on the use of transformational leadership variables, culture diversity, work satisfaction, organizational citizenship behavior, and employee performance. The novelty presented from this research explains that although most employees have different cultural backgrounds if supported by a fair and wise application of transformational leadership, it will encourage job satisfaction.